DOUBLE BURDEN PETANI PEREMPUAN DALAM KELUARGA DI DESA CUT REUBEE DELIMA KABUPATEN PIDIE - Kamilna Kamilna; Novita sari; Muliawati Muliawati (Journal of Political Sphere, 2022)
ABSTRACTInequality of division of labor between men and women in a family poses a double burden. This research was conducted in Cut Reubee Village, Delima Subdistrict, Pidie Regency, which still adheres to the patriarchal system, which causes one of the parties in the family to experience a double burden in the family, especially for women who also work as farmers. This study aims to describe and know the strategies of women farmers in facing the reality of the double burden of women farmers in the family. The research uses nurture theory which suggests that socio-cultural constructions themselves cause role differences between men and women. This research uses a descriptive method with a qualitative approach. Data were collected through observations, interviews, and documentation. Informants in this study were determined according to certain criteria tailored to the research topic. The results showed that Cut Reubee Delima Village women farmers did more activities than men. The double burden causes women farmers to experience various problems, especially health issues in carrying out this role. The strategy of women farmers in facing the double burden in the family is to manage time as wisely as possible. Therefore, there needs to be concrete action from various parties to minimize gender discrimination between men and women starting with establishing a pattern of fair labor sharing relations in the family between men and women.Keywords: double burden, women farmer, family